Pembaharuan Hukum Waris Adat dalam Putusan Pengadilan (Penghormatan Identitas Budaya Vs Perkembangan Zaman) - Victor Imanuel W. Nalle (Fakultas Hukum Universitas Gadjah Mada, 2018)
AbstractSupreme Court decisions have established that daughters have the right to inherit their fathers’ property. It is contrary with principle of inheritance on adat law, especially in patrilineal communities. Therefore this article analysis legal reasoning in Supreme Court decisions within equality between men and women in inheritance cases and their implications to cultural identities. Analysis in this article uses case approach to Supreme Court decisions in 1974 to 2016. The case approach in this article found that Supreme Court decisions use the perspective of human rights to criticize inequality between men and women on inheritance law in adat law. However, Article 28I par. 3 the 1945 Constitution of the Republic of Indonesia states that cultural identities and rights of traditional communities shall be respected in accordance with the “development of times and civilisations”. This facts show that the definition of